2021
DOI: 10.1364/oe.446725
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous detection of K, KOH, and KCl in flames and released from biomass using photofragmentation TDLAS

Abstract: Gaseous potassium (K) species released from biomass during thermochemical conversion pose challenges to reactors and human health. Photofragmentation tunable diode laser absorption spectroscopy (PF-TDLAS) was used for simultaneous, high-dynamic range measurements of atomic K, potassium hydroxide (KOH) and potassium chloride (KCl) in flat flames seeded with KCl salt. An expression for the PF-TDLAS signal is presented and experimentally verified. Axial K species concentration profiles recorded at fuel-air equiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 34 publications
3
10
0
Order By: Relevance
“…This is reasonable as (i) the particle temperature during char conversion is higher, (ii) most of the K in the fuel is released after the devolatilization stage, and (iii) the gas temperature in the vicinity of the particle is closer to the flame temperature. ,, Beyond a height above the particle surface of about 5 mm (corresponding to HAP 8 mm), the LOS average concentration decreased to below 1 ppm (Figure ). This is in good agreement with previous measurements of K species above wheat straw particles in a CH 4 /air flame, the small differences in absolute values possibly explained by the different particle size used.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…This is reasonable as (i) the particle temperature during char conversion is higher, (ii) most of the K in the fuel is released after the devolatilization stage, and (iii) the gas temperature in the vicinity of the particle is closer to the flame temperature. ,, Beyond a height above the particle surface of about 5 mm (corresponding to HAP 8 mm), the LOS average concentration decreased to below 1 ppm (Figure ). This is in good agreement with previous measurements of K species above wheat straw particles in a CH 4 /air flame, the small differences in absolute values possibly explained by the different particle size used.…”
Section: Resultssupporting
confidence: 92%
“…As can be seen in Figure a, there are regions of high absorbance around the Pt plate edge, extending even below the plate, and the absorbance rapidly decreases as a function of HAP. The accumulation of atomic K near the plate edge has been observed in previous computational fluid dynamics (CFD) simulations and can be explained by recirculation due to the obstruction of the flow by the plate . Above approximately 4 mm HAP, the absorbance resembles a Gaussian shape as a function of horizontal position.…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…The KCl release continued during the ash-cooking stage, but at a lower rate compared to the char combustion. More recently, Thorin et al 33 , 34 developed photofragmentation tunable diode laser absorption spectroscopy (PF-TDLAS) for simultaneous measurements of K, KOH, and KCl in both combustion and gasification, the latter usually characterized by optically thick conditions for K. The technique was applied for the detection of the three K species in a 140 kW EFG. 35 It was shown that the effects of small differences in fuel composition on the potassium release can be resolved by the PF-TDLAS method and that the obtained K species concentrations agreed reasonably well with the results from the thermodynamic equilibrium calculation.…”
Section: Introductionmentioning
confidence: 99%
“…Many semiconducting materials are used for conductometric H 2 sensing, including graphene-based materials, transition metal dichalcogenides, and metal oxides [ 5 , 6 ]. Many different sensing technologies have been developed for H 2 sensing [ 7 , 8 , 9 ] and semiconductor-based H 2 sensors mainly present high sensitivity, quick response, and good stability based on their physical and electrochemical characteristics [ 10 , 11 , 12 , 13 , 14 ]. Commonly, the exceptional physical, optical, and electrical properties of 2D semiconductors, such as high surface to volume ratios and numerous active sites, lead to promising gas sensing performance (i.e., gas selectivity, excellent response, durability, and quick response and recovery) because of a change in charge density concentration near or on the sensing layer [ 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%